Current diagnosis, risk stratification and treatment paradigms in newly diagnosed multiple myeloma. (2021) - Ravi, Gayathri; Gonsalves, Wilson I.
Highlights: The diagnostic and treatment paradigms in multiple myeloma have evolved over the last two decades. Various prognostic features have been delineated to risk stratify newly diagnosed multiple myeloma patients. Induction therapies utilizing novel agent therapies provide high levels of response and this has improved overall survival. High dose chemotherapy followed by stem cell rescue and maintenance therapy remains an active therapy for the treatment of multiple myeloma. Future clinical trials incorporating novel small molecule inhibitors and immunotherapeutic approaches into the treatment armamentarium are critical for improving the outcomes of patients with multiple myeloma.